2017
DOI: 10.1111/muse.12147
|View full text |Cite
|
Sign up to set email alerts
|

The Acropolis Museum: Contextual Contradictions, Conceptual Complexities

Abstract: Drawing on the public debates on the location of the new site museum exhibiting the sculptures and other artefacts of the iconic Athenian Acropolis, the author highlights the complexity of integrating a new site‐specific museum to a historically charged urban monumental and cultural landscape. By presenting 13 alternative viewpoints on the topic of this museum's location together with the respective museological concepts debated during the planning stage, this paper delineates the various conceptual hierarchie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The situation in the archaeological museum sector has also worsened during that period (Howery 2013)-although, I would argue, not so dramatically as the media would have the public believe. It merely brought the pre-existing weaknesses to light and made them more visible (Filippopoulou 2015). Gazi, who studied the crisis's impact on archaeological museums, also concluded that, despite a number of individual initiatives, the crisis has accentuated long-standing structural deficiencies relating to heritage management as a whole.…”
Section: Evaluating Museum Attendance In Greecementioning
confidence: 99%
“…The situation in the archaeological museum sector has also worsened during that period (Howery 2013)-although, I would argue, not so dramatically as the media would have the public believe. It merely brought the pre-existing weaknesses to light and made them more visible (Filippopoulou 2015). Gazi, who studied the crisis's impact on archaeological museums, also concluded that, despite a number of individual initiatives, the crisis has accentuated long-standing structural deficiencies relating to heritage management as a whole.…”
Section: Evaluating Museum Attendance In Greecementioning
confidence: 99%